Malaysian identity in design education: furniture and jewellery products / Marzuki Ibrahim ...[et al.] - Ibrahim, Marzuki; Daud, Mohd Zamani; A.Tarmizi, M. Shahrul Hisham; Badaruddin, M. Iqbal (Unit Penerbitan Universiti Teknologi MARA, Kelantan, 2017)
Abstract –Incorporating issues of Malaysian identity in design education has become an important goal for educators in Malaysia recently. From theperspectiveofdesign students, many of them are constantly facing the dilemma of how to integrate identity in their design works.This paper reviews the literature that focuses on Malaysian identity. It begins with the development of education design in Malaysia followed by a review of furniture and jewellery design in Malaysia. This paper highlights a number of selected design works of furniture and jewellery design taken from the most recent winnersof design competitions and students’ project designswhichcarry the Malaysian identity in their designs.This paper concludes that design students as well as manufacturers have the responsibility of ensuring that furniture and jewellery products from Malaysia have the inherent look that is Malaysian by using local raw materials, applying Malaysian symbols and incorporating the cultural activities of Malaysians into the products. Besides bringing awareness in matters related to the Malaysian identity, this paper is also useful for design students, designers and manufacturers as a guideline to incorporate national identity into their designs